A SHARIAH-BASED EXAMINATION OF SELECTED JAIZ BANK PRODUCTS - Folorunsho, Ahmad Hussein; Murtadha, Ahmad Olusola; Belgore, Usman Kola (Journal of Shariah Law Research, 2025)
Jaiz Bank is a full-fledged Islamic bank licenced and operating in Nigeria. The bank is authorized to operate throughout the federation and offers a range of products in designing its savings, current, and other banking services. This research focused on examining the Shariah compliance of some of these products. In particular, it analysed the products adopted in designing the bank’s savings and current accounts. It also examined some Jaiz Bank products developed from murābahah-related contract, which have attracted criticisms from certain scholars and Islamic clerics in Nigeria. The compliance of some of these products with the principles of Shariah has generated debates and controversies as to whether the products designed from the traditional Islamic contracts truly align with the intention of the Law-Giver. It is often asserted that not all Islamic banks offer, genuinely, Islamic or Shariah-compliant product. Thus, this research became necessary to examine the Shariah compliance of some products offered by Jaiz Bank. Undoubtedly, there are several studies on Islamic finance, particularly on Islamic banking products. However, this research distinguishes itself from the existing studies focusing, specifically, on selected Jaiz Bank products and analysing their various several terms in the light of Shariah. The doctrinal method of research is adopted to examine the bank’s products. The terms and conditions of these products are analysed through the lens of Shariah. Upon the analysis, the research finds that the products used in designing the bank’s savings and current accounts substantially comply with shariah. It, however, observes that the terms of the savings account do not accommodate the two-tier mudārabah structure commonly practiced by Islamic banks. Meanwhile, the murābahah-related products adopted by the bank remain subjects of juristic disagreement. This research aligns with the juristic view that considers such murābahah-based products - as adopted by Islamic banks including Jaiz Bank – to be inconsistent with Shariah. Nevertheless, this research refrain from categorically declaring these products non-compliant, as in matters of ijtihād, no single opinion is deemed superior to another. Therefore, the study profers recommendations aimed at enhancing full compliance of the selected Jaiz Bank products.